Plan Ahead for Efficiency: This Thing Called Plan of Work - Leo R. Fehlhafer (Journal of Applied Communications, 1970)
Tom McCormick, writing in the January-March 1970 issue of ACE, hit a rather sore point when he wrote that editors need to get more mileage out of the work they do.